Comprehensive Mechanism of Gene Silencing and Its Role in Plant Growth and Development - El-Sappah, Ahmed H.; Yan, Kuan; Huang, Qiulan; Islam, Md. Monirul; Li, Quanzi; Wang, Yu; Khan, Muhammad Sarwar; Zhao, Xianming; Mir, Reyazul Rouf; Li, Jia; El-Tarabily, Khaled A.; Abbas, Manzar (Frontiers in Plant Science, 2021)
Gene silencing is a negative feedback mechanism that regulates gene expression to define cell fate, regulates metabolism and gene expression throughout the life of an organism. In plants, gene silencing occurs via Transcriptional Gene Silencing (TGS) and Post-Transcriptional Gene Silencing (PTGS). TGS obscures transcription via methylation of a 5́UTR, while PTGS causes methylation of coding region resulted in transcript degradation. In this review, we summarized the history and molecular mechanisms of gene silencing and underlined its specific role in plant growth and crop production.